2019
DOI: 10.1051/sicotj/2019026
|View full text |Cite
|
Sign up to set email alerts
|

Short-term results (1 year) of vented versus solid polyetheretherketone anchors in treatment of rotator cuff tears

Abstract: Background: Due to the rotator cuff retear after being surgically repaired, some strategies have been developed. The authors verified that the possibility of polyetheretherketone (PEEK) vented anchors promoted a better clinical and healing process than PEEK solid anchors. Methods: A prospective and randomized study was designed with 38 patients treated with PEEK anchors, 18 of whom with vented anchors and 20 with solid ones. Demographic, clinical and radiologic data were collected before and during surgery (ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Three of the 4 studies were included in the meta-analysis. 19,32,33 In summary, the included clinical studies have not demonstrated clear significant clinical benefit of vented anchors over nonvented anchors. The pooled retear rates for the 3 studies included in the meta-analysis were 22.5% (18/80) for the interventional group and 27.8% (59/212) for the control group.…”
Section: Results From Clinical Studies Of Vented Anchorsmentioning
confidence: 93%
See 4 more Smart Citations
“…Three of the 4 studies were included in the meta-analysis. 19,32,33 In summary, the included clinical studies have not demonstrated clear significant clinical benefit of vented anchors over nonvented anchors. The pooled retear rates for the 3 studies included in the meta-analysis were 22.5% (18/80) for the interventional group and 27.8% (59/212) for the control group.…”
Section: Results From Clinical Studies Of Vented Anchorsmentioning
confidence: 93%
“…4,18,19,24,28,[31][32][33]37 All 6 randomized controlled trials included in the study achieved a good score based on the CLEAR-NPT criteria. 4,19,24,28,33,37 All 3 nonrandomized comparative studies included in the meta-analysis achieved a "B" rating, according to the MINORS criteria, indicating a low risk of bias. 18,31,32 Four noncomparative studies were evaluated using the MINORS criteria.…”
Section: Results Of the Methodologic Quality Assessmentmentioning
confidence: 99%
See 3 more Smart Citations